Physical activity and physical activity induced energy expenditure in humans: measurement, determinants, and effects - Westerterp, Klaas R. (Frontiers in Physiology, 2013)
Physical activity is defined as any bodily movement produced by skeletal muscles that results in energy expenditure. The doubly labelled water method for the measurement of total energy expenditure, in combination with resting energy expenditure, is the reference for physical activity under free-living conditions. To compare the physical activity level (PAL) within and between species, total energy expenditure is divided by resting energy expenditure resulting in a figure without dimension. The PAL for sustainable lifestyles ranges between a minimum of 1.1-1.2 and a maximum of 2.0-2.5. The average PAL increases from 1.4 at age 1 year to 1.7-1.8 at reproductive age and declines again to 1.4 at age 90 year. Exercise training increases PAL in young adults when energy balance is maintained by increasing energy intake. Professional endurance athletes can reach PAL values around 4.0. Most of the variation in PAL between subjects can be ascribed to predisposition. A higher weight implicates higher movement costs and less body movement but not necessarily a lower PAL. Changes in physical activity primarily affect body composition and to a lesser extent body weight. Modern man has a similar PAL as a wild mammal of a similar body size.